HANDS-ON WEB PENETRATION TESTING WITH METASPLOIT;THE SUBTLE ART OF USING METASPLOIT 5.0 FOR WEB APPLICATION EXPLOITATION - HARPREET SINGH; HIMANSHU SHARMA (PACKT PUBLISHING, 2020)
Metasploit is one of the best frameworks used for enumeration and exploitation of vulnerabilities. This book will not only give you a practical understanding of Metasploit but will also cover some less known modules and auxiliaries for pentesting Web Applications.